The Influence of Customer Satisfaction on Consumer Purchasing Decisions on Catering Products at CV. Wery Group Gunungsitoli City - Zendrato, Lois Ihcasia; Laia, Otanius; Harefa, Idarni; Buulolo, Nanny Artatina (Sean Institute, 2025)
This study aims to determine the influence of customer satisfaction on consumer purchasing decisions for catering products at CV. Wery Group Gunungsitoli City. The research method used is a quantitative approach with statistical analysis to measure the relationship between customer satisfaction (X) and purchasing decisions (Y). Based on the determination test results, the Adjusted R Square value was found to be 0.672. This indicates that the customer satisfaction variable (X) explains 67.2% of the purchasing decision variable (Y) after adjusting for the sample size and independent variables used. Meanwhile, the remaining 32.8% is influenced by other factors not included in this study. The findings of this study suggest that the higher the level of customer satisfaction, the greater the likelihood of repeat purchases of catering products from CV. Wery Group. Therefore, the company must continuously improve service quality and product standards to maintain and enhance consumer purchasing decisions.